A prosurvival and proangiogenic stem cell delivery system to promote ischemic limb regeneration. (February 2016) - Xu, Yanyi; Fu, Minghuan; Li, Zhihong; Fan, Zhaobo; Li, Xiaofei; Liu, Ying; Anderson, Peter M.; Xie, Xiaoyun; Liu, Zhenguo; Guan, Jianjun
Graphical abstract: Abstract: Stem cell therapy is one of the most promising strategies to restore blood perfusion and promote muscle regeneration in ischemic limbs. Yet its therapeutic efficacy remains low owing to the inferior cell survival under the low oxygen and nutrient environment of the injured limbs. To increase therapeutic efficacy, high rates of both short- and long-term cell survival are essential, which current approaches do not support. In this work, we hypothesized that a high rate of short-term cell survival can be achieved by introducing a prosurvival environment into the stem cell delivery system to enhance cell survival before vascularization is established; and that a high rate of long-term cell survival can be attained by building a proangiogenic environment in the system to quickly vascularize the limbs. The system was based on a biodegradable and thermosensitive poly(N-Isopropylacrylamide)-based hydrogel, a prosurvival and proangiogenic growth factor bFGF, and bone marrow-derived mesenchymal stem cells (MSCs). bFGF can be continuously released from the system for 4 weeks. The released bFGF significantly improved MSC survival and paracrine effects under low nutrient and oxygen conditions (0% FBS and 1% O2 ) in vitro. The prosurvival effect of the bFGF on MSCs was resulted from activating cell Kruppel-like factor 4 (KLF4) pathway. When transplanted into the ischemic limbs, the system dramatically improved MSC survival. Some of the engrafted cells were differentiated into skeletal muscle and endothelial cells, respectively. The system also promoted the proliferation of host cells. After only 2 weeks of implantation, tissue blood perfusion was completely recovered; and after 4 weeks, the muscle fiber diameter was restored similarly to that of the normal limbs. These pronounced results demonstrate that the developed stem cell delivery system has a potential for ischemic limb regeneration. Statement of significance: Stem cell therapy is a promising strategy to restore blood perfusion and promote muscle regeneration in ischemic limbs. Yet its therapeutic efficacy remains low owing to the inferior cell survival under the ischemic environment of the injured limbs. To increase therapeutic efficacy, high rate of cell survival is essential, which current approaches do not support. In this work, we tested the hypothesis that a stem cell delivery system that can continuously release a prosurvival and proangiogenic growth factor will promote high rates of cell survival in the ischemic limbs. The prosurvival effect could augment cell survival before vascularization is established, while the proangiogenic effect could stimulate quick angiogenesis to achieve long-term cell survival. Meanwhile, the differentiation of stem cells into endothelial and myogenic lineages, and cell paracrine effects will enhance vascularization and muscle regeneration.